The sustainability curriculum : the challenge for higher education - Blewitt, John, 1957-; Cullingford, Cedric (Earthscan, 2004)
The links between education and sustainable development are deepening although subject to much controversy and debate. The success of the sustainability discourse depends both on the pedagogic and research functions of higher education. Similarly for higher education itself to remain relevant and engaged it faces pressure not only to integrate the insights and lessons drawn from the perspective of sustainable development but also to be responsive to scrutiny of its own practices in relation to s.